Technology, Mechanization, and the Life and Death of a Kansas Common Pasture: The Story of the Westmoreland Common Pasture, Westmoreland, Pottawatomie County, Kansas, 1860-1940 - McCoy, Travis J. (Kansas State University. Dept. of History, 2011)
Many small towns in Kansas had a shared dairy commons. The author of this study connects the commons in Westmoreland, Rock Creek Valley, with the strong German and Sudetenland settler culture; he also traces the life of the commons and its eventual decline to milk trucks able to deliver bottled milk by the 1930s. By World War II, the commons was in its final days. The writer locates the original site and provides photographs.
Keywords: Pottawatomie County; Westmoreland; Common pasture; German culture; Dairy cows